2022
DOI: 10.2147/pgpm.s367978
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Metastases from Lung Adenocarcinoma Disappeared After Molecular Targeted Therapy: A Successfully Clinical Treatment Experience

Abstract: Introduction Molecular targeted therapy has shown certain therapeutic effects on various cancer types, especially lung cancer. Here, we report a case of a patient with unresectable non-small cell lung cancer (NSCLC) with bone metastases and metastatic lesions that disappeared after molecular targeted therapy. Patient Information A 49-year-old male patient’s chest CT scan showed a patchy, slightly high-density shadow on the upper lobe of the left lung with an unclear bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…A number of therapeutic agents such as anthocyanins, ginsenoside-R3, dexmedetomidine hydrochloride, berberine, sorafenib, 17β-Estradiol, phenylpyridinium, tetrahydroxy stilbene glycoside, cisplatin, resveratrol, sulforaphane and liraglutide have been found to affect expression of non-coding RNAs/SIRT1 axes ( Table 4 ). For instance, experiments in animal model of asthma have shown that anthocyanins suppresses inflammatory responses in airways through decreasing activity of NF-κB pathway via the miR-138-5p/SIRT1 axis ( Liu Y. et al, 2022 ). Moreover, ginsenoside Rg3 can alleviate sepsis-related hepatic injury through modulation of TUG1/miR-200c-3p/SIRT1 axis ( Wu P. et al, 2021 ).…”
Section: Sirt1-interacting Lncrnasmentioning
confidence: 99%
“…A number of therapeutic agents such as anthocyanins, ginsenoside-R3, dexmedetomidine hydrochloride, berberine, sorafenib, 17β-Estradiol, phenylpyridinium, tetrahydroxy stilbene glycoside, cisplatin, resveratrol, sulforaphane and liraglutide have been found to affect expression of non-coding RNAs/SIRT1 axes ( Table 4 ). For instance, experiments in animal model of asthma have shown that anthocyanins suppresses inflammatory responses in airways through decreasing activity of NF-κB pathway via the miR-138-5p/SIRT1 axis ( Liu Y. et al, 2022 ). Moreover, ginsenoside Rg3 can alleviate sepsis-related hepatic injury through modulation of TUG1/miR-200c-3p/SIRT1 axis ( Wu P. et al, 2021 ).…”
Section: Sirt1-interacting Lncrnasmentioning
confidence: 99%
“…), additional small lung nodules have been subjected to pathological or genetic molecular diagnosis ( 4 , 5 ). In addition, the TNM staging of lung cancer has been optimized in multiple ways ( 6 , 7 ). So, interest in thoracic surgery for sublobar resection for early-stage lung cancer has increased again.…”
Section: Introductionmentioning
confidence: 99%